Password: Red hot - Pettit, Kristen; Riordan, Robin (New York : HarperEntertainment, 2003)
Special agents, Misty and Amber are sent to England to stop the evil Clive Hedgmorton-Smythe who plans to use a satellite to block out the sun permanently and cause the next ice age.
All Ages.
Keywords: Olsen, Mary-Kate, -- 1986- -- Fiction; Olsen, Ashley, -- 1986- -- Fiction; Twins -- Juvenile fiction; Sisters -- Juvenile fiction; England -- Juvenile fiction